Characterization of intergranular corrosion defects in a 2024 T351 aluminium alloy. (1st May 2017) - de Bonfils-Lahovary, Marie-Laetitia; Laffont, Lydia; Blanc, Christine
Graphical abstract: Highlights: Intergranular corrosion defects were analyzed by electron microscopy techniques. Dissolution of Cu-rich intermetallics occurred at corroded grain boundaries. Cu was incorporated into the amorphous alumina film at corroded grain boundaries. A metallic Cu-rich layer was identified at the oxide/metal interface. Abstract: Intergranular corrosion defects formed after a 24 h immersion in a 1 M NaCl solution in a 2024-T351 Al alloy were characterized using a combination of electron microscopy techniques. Results showed the dissolution of intergranular Cu-rich precipitates all along the corroded grain boundaries. Cu species were incorporated inside the amorphous alumina oxide film identified in the corroded grain boundaries leading to the formation of structural defects in the oxide film. A 10–200 nm-thin metallic Cu-rich layer was also observed at the oxide/metal interface and at the tip of the intergranular corrosion defect.